The Role of TNCs in Poland's East-West Trade - Cieślik, Jerzy; Sosnowski, Boguslaw (Journal of International Business Studies, 1985)
This paper examines empirically the scale of transnational corporation (TNC) involvement in the area of economic cooperation between Poland and developed market economy countries. Data were collected on TNC involvement in commodity turnover, technology transfers and industrial cooperation, and on the establishment of representation offices. The findings strongly underline the importance of TNCs as trading partners in key areas in the acquisition of high technology and equipment and in industrial cooperation. The popular view, however, that the flow of East-West trade is dominated by a handful of large TNCs was found to be overemphasized.